"What an eye-opener" – a qualitative study of vulnerable citizens participating in a municipality-based intervention. Issue 1 (1st January 2018) - Ilvig, Pia Maria; Kjær, Michaela; Jones, Dorrie; Christensen, Jeanette Reffstrup; Andersen, Lotte Nygaard
ABSTRACT: Purpose : To explore how psychologically vulnerable citizens experienced performing their everyday-life activities, identify activities experienced as particularly challenging and evaluate the significance of the Acceptance and Commitment Theory-based (ACT)-based program, Well-being in Daily Life, had on the participants everyday-life activities. Methods : Semi-structured interviews were conducted with eight participants from the Well-being in Daily Life program. Data were analysed using Systematic Text Condensation. Results and Conclusion : The participants experienced anxiety, fatigue, lack of structure, and chaos when performing their everyday-life activities; in addition to being uncertain about the limitations of their own resources. Furthermore, balancing between demands and resources was challenging, also leading to uncertainty and identity conflicts that contributed to the participants' concerns about re-entering the workforce. The program enabled the participants to develop social skills and trust which contributed to providing the participants with confidence, individually-tailored-possibilities for developing new competencies and courage; thus, facilitating their recovery process.